Динаміка морфофункціональних зрушень підшлункової залози та рівень цитокинів у потомства щурів внаслідок дії хронічного стресу = The dynamics of the morphofunctional changes of the offspring-rats' pancreases and level of cytokinins resulting from an action of the chronic stress - O. Nikolayeva; E. Pavlova; V. Sirenko; M. Kovaltsova; I. Sulhdost (Kazimierz Wielki University, 2016)
Nikolayeva O., Pavlova E., Sirenko V., Kovaltsova M., Sulhdost I. Динаміка морфофункціональних зрушень підшлункової залози та рівень цитокинів у потомства щурів внаслідок дії хронічного стресу = The dynamics of the morphofunctional changes of the offspring-rats' pancreases and level of cytokinins resulting from an action of the chronic stress. Journal of Education, Health and Sport. 2016;6(6):279-290. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55416 http://ojs.ukw.edu.pl/index.php/johs/article/view/3578   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016.   УДК 616.37-091.8-092.9:613.24/.25:613.65:612.015.11   ДИНАМІКА МОРФОФУНКЦІОНАЛЬНИХ ЗРУШЕНЬ ПІДШЛУНКОВОЇ ЗАЛОЗИ ТА РІВЕНЬ ЦИТОКИНІВ У ПОТОМСТВА ЩУРІВ ВНАСЛІДОК ДІЇ ХРОНІЧНОГО СТРЕСУ   О. В. Ніколаєва, О. О. Павлова, В. А. Сіренко, М. В. Ковальцова, І. О. Сулхдост   Харківський національний медичний університет. Харків. Україна   The Dynamics Of The Morphofunctional Changes Of The Offspring-Rats' Pancreases and Level Of Cytokinins Resulting From An Action Of The Chronic Stress   O. Nikolayeva, E. Pavlova, V. Sirenko, M. Kovaltsova, I. Sulhdost   Kharkiv National Medical University, Kharkov, Ukraine   Introduction. The pathology of the pancreas caused by the stress is an actual problem of medicine. The purpose of the study was describe of characteristics morphofunctional state of the pancreas of babe-rats' and to analyzed pro-inflammatory and anti-inflammatory cytokines balance. Materials and Methods. We studied morphological changes of pancreas of offspring-rats' using histological, cytochemical, cytomorphometric and biochemical methods. We studied immunological status using biochemical methods. We studied the level of interleukin-12 and interleukin-4 in the blood. The core group of mother-rats was exposed to chronic stress immobilization. The comparison group consisted of animals that led ordinary life. For the rats, the experiment was stopped immediately after the birth of offspring in compliance with the ethical principles. Results. Stress during pregnancy in rats affects the morphology and function of the pancreas in the offspring. Symptoms of morphofunctional disorders are obvious even in the pancreas of newborn rats. There are reduced acini and islets of Langerhans, immaturity parenchymal area, edema, fibrosis, degenerative changes in the nuclei and cytoplasm exocrine and endocrine cells, decrease morphofunctional state of the same part of pancreas cell, violation of geodynamics. Most of them not only saves up until they are two months of age, but has a negative trend of growth severity: reducing the relative amount of parenchymal acini area, number and area of the islets of Langerhans, the number of endocrine cells in them, apiaries lipomatosis stroma. We also noticed simultaneous launch of compensatory-adaptive processes in the endocrine pancreas in the form of hypertrophy of single islets of Langerhans. The rats in all groups are diagnosed as having identical tendencies of cytokines change; significant buildup of pro-inflammatory interleukin-12 and reduction of anti-inflammatory interleukin-4 which indicates predominant involvement in pathogenesis of violation of pancreas cell component of immune system. Conclusions. The results suggest that chronic stress of pregnant rats is a significant risk factor for future chronic pathology of the pancreas rats-offspring. Keywords: chronic stress immobilization, pancreas, rats, interleukin, experiment.   ДИНАМИКА МОРФОФУНКЦИОНАЛЬНЫХ НАРУШЕНИЙ ПОДЖЕЛУДОЧНОЙ ЖЕЛЕЗЫ И УРОВЕНЬ ЦИТОКИНОВ У ПОТОМСТВА КРЫС ВСЛЕДСТВИЕ ДЕЙСТВИЯ ХРОНИЧЕСКОГО СТРЕССА   О. В. Николаева, Е. А. Павлова, В. А. Сиренко, М. В. Ковальцова, И. А. Сулхдост   Харьковский национальный медицинский университет, Харьков, Украина   Проведено морфологическое и биохимическое исследование влияния хронического стресса матери на морфофункциональные особенности поджелудочной железы новорожденного, одномесячного и двухмесячного потомства. Обнаружено, что пренатальный стресс приводит к морфофункциональной перестройке поджелудочной железы крысиного потомства, с развитием стойких и прогрессирующих в динамике деструктивных изменений в ациноцитах и эндокриноцитах, к снижению морфофункциональной активности части клеточных элементов, к развитию гемодинамических нарушений у части животных. Выяснено, что у разновозрастного крысиного потомства наблюдается системный гуморальный ответ в виде дисбаланса цитокинов с преобладанием  маркерного цитокина Th1-лимфоцитов (интерлейкина-12), что свидетельствует о вовлечении в патогенезе повреждения поджелудочной железы клеточной цепи иммунитета. Установлено, что цитокиновый дисбаланс негативно влияет на внутриклеточный метаболизм панкреацитов, их экзокринную и эндокринную секреторную активность, и, вероятно, может еще больше усиливать повреждения поджелудочной железы у экспериментальных животных.           Ключевые слова: ациноциты, эндокриноциты, иммобилизация, интерлейкины, крысята, эксперимент.